(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this study, ANN models are applied to analyze malaria cases in children under the age of 15 confirmed at Gweru Provincial Hospital (GPH). The used data covers the period January 2010 to December 2019 while the out-of-sample period ranges over the period Janaury 2020 to December 2021. The residuals as well as the evaluation criteria (Error, MSE, MAE) of the applied model show that the model is stable and suitable for forecasting the series under consideration. The results basically indicated that over the out-of-sample period malaria cases will range between 1 and 4 cases. These are relatively low figures and quite manageable for a referral hospital such as GPH. The study recommends the following: through its community-based programs, GPH should create public awareness on malaria and engage in indoor residual spraying amongst other initiatives; GPH should make sure there are adequate malaria commodities in stock, especially essential malaria medicines.